Shear Strength of the Groove of Precast Concrete H-Posts - Gautam, Bishnu Prasad; Chaudhary, Dip Roshan; Gautam, Dipendra (Journal of Engineering Technology and Planning, 2023)
The precast concrete market is increasing globally with an estimated economy of 107.83 billion US dollars in 2018 and a growth rate of 5.7%. Boundary wall is one of the popular applications of precast concrete. H-posts used in boundary walls have plain concrete grooves and their shear strength is not studied well. While theoretical shear resistance of the groove based on concrete codes is greater than the likely wind load, this study experimentally validates the shear strength of such grooves by performing structural testing. Five test series with two repetitions are tested. Two grades of concrete are tested with plain grooves and grooves having reinforcement studs. Shear resistance of the grooves is at least 8 times greater than the maximum wind load. The ultimate failure occurs at the stem of the grooves for the plain concrete grooves, but panels fail in bearing for the specimens with shear studs at grooves.